A blood‐based nutritional risk index explains cognitive enhancement and decline in the multidomain Alzheimer prevention trial. Issue 1 (1st January 2019) - Bowman, Gene L.; Dodge, Hiroko H.; Guyonnet, Sophie; Zhou, Nina; Donohue, Juliana; Bichsel, Aline; Schmitt, Jeroen; Hooper, Claudie; Bartfai, Tamas; Andrieu, Sandrine; Vellas, Bruno; et al.
Abstract: Introduction: Multinutrient approaches may produce more robust effects on brain health through interactive qualities. We hypothesized that a blood‐based nutritional risk index (NRI) including three biomarkers of diet quality can explain cognitive trajectories in the multidomain Alzheimer prevention trial (MAPT) over 3‐years. Methods: The NRI included erythrocyte n‐3 polyunsaturated fatty acids (n‐3 PUFA 22:6n‐3 and 20:5n‐3), serum 25‐hydroxyvitamin D, and plasma homocysteine. The NRI scores reflect the number of nutritional risk factors (0–3). The primary outcome in MAPT was a cognitive composite Z score within each participant that was fit with linear mixed‐effects models. Results: Eighty percent had at lease one nutritional risk factor for cognitive decline (NRI ≥1: 573 of 712). Participants presenting without nutritional risk factors (NRI=0) exhibited cognitive enhancement ( β = 0.03 standard units [SU]/y), whereas each NRI point increase corresponded to an incremental acceleration in rates of cognitive decline (NRI‐1: β = −0.04 SU/y, P = .03; NRI‐2: β = −0.08 SU/y, P < .0001; and NRI‐3: β = −0.11 SU/y, P = .0008). Discussion: Identifying and addressing these well‐established nutritional risk factors may reduce age‐related cognitive decline in older adults; an observation that warrants further study. Highlights: Multi‐nutrient approaches may produce more robust effects through interactive properties Nutritional risk index can objectively quantify nutrition‐related cognitive changes Optimum nutritional status associated with cognitive enhancement over 3‐years Suboptimum nutritional status associated with cognitive decline over 3‐years Optimizing this nutritional risk index may promote cognitive health in older adults